Evaluasi Pakan Sumber Energi Berbasis Sorgum, Gaplek, dan Sagu sebagai Substitusi Jagung dalam Ransum Ayam Broiler: valuation of energy source feed based on sorghum, cassava and sago as a substitute for corn in Broiler chicken rations - Heri Ahmad Sukria; Sazli Tutur Risyahadi; Ryzal Satria Aditama; Muhammad Hisyam Salahuddin (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
This study aimed to examine local feed ingredients such as sorghum, cassava and whole sago as the substitution of corn in the ration through the growth of broiler chickens. The growth observed variables were feed consumption, final body weight, body weight gain, feed conversion and mortality during growth from 1-5 week of age. The experimental design conducted was a completely randomized design with 4 treatments, namely commercial rations (P0), rations containing sorghum (P1), rations containing cassava (P2) and rations containing whole sago (P3). Each treatment consisted of 3 replicates in a high-density cage of 16-17 chickens m-2 for each replication. The total number of chickens used for the experiment were 200 chickens. The results showed that the mean final body weight and weight gain was significantly lower (p<0.01) than that of control treatment, whilst feed consumption was not significantly different. Growth of the chickens of P1, P2 and P3 treatments was not significantly different. Rations based on sorghum, cassava or whole sago as the 100% substitution of corn in broiler chickens could not facilitate the growth as well as broiler chickens in factory feeds. Key words: broilers, cassava chip, sago, sorghum